DAYA HAMBAT BERKUMUR EKSTRAK DAUN SALAM (SYZYGIUM POLYANTHUM) TERHADAP PEMBENTUKAN PLAK PADA MAHASISWA JURUSAN KEPERAWATAN GIGI DI BUKITTINGGI - Dewi Rosmalia (Jurnal Sehat Mandiri, 2021)
Bay leaves (Syzgium Polyanthum) contain flavonoids, tannins and essential oils which act as antibacterial. Plaque contains bacteria that stick closely to the surface of the teeth which can cause disease in the hard tissues of the teeth and the supporting tissues of the teeth. Plaque control is carried out mechanically and chemically, on of which is gargling bay leaf extract. Plaque measurement using the plaque index. The research objective was to determine the inhibition of gargling of bay leaf extract against plaque formation. This study used a quasi experimental method wth a post test control group design. The sampling technique was simple random sampling, the number of sample was determined Fredere’s formula, the sample devided into 3 groups, each group conssiting of 9 respondents.Group 1 rinsed with bay leaf extract, group 2 rinsed with antiseptic mouthwash and group 3 rinsed with aquadest. Data were tested by using Annova test. The result showed that the average plaque index after rinsing the bay leaf extract was 1.056, the average plaque indexgargling antiseptic mouthwash was 2.478, and the average plaque index after gargling with aquadest was 2167.The significance value is 0.178 and f count > f table (6.238> 3.403). The conclusion was garglingbay leaf extract wwas more effective in inhibiting plaque formation. It is recommended to use bay leaf extract as a mouthwash to maintain oral health.